Arrhythmias in two patients with left ventricular bypass transplants. - Kennelly, B M (1976)
Two patients who underwent left ventricular bypass transplants are described. Both patients sustained postoperative rhythm disturbances of their own hearts during sinus rhythm of the donor hearts. Illustrative examples of atrial flutter, ventricular flutter, ventricular fibrillation, blocked atrial extrasystoles, and double ventricular parasystole in the recipient hearts are presented. The patients tolerated all these arrhythmias well during uninterrupted sinus rhythm in the donor heart. The problems in interpretation of arrhythmias in the presence of two hearts are discussed.